Indicadores de inovação e tecnologia: O arranjo produtivo local de apicultura no nordeste paraense - Monteiro, Edney Saraiva (2013)
The aim of this study was to characterize the local productive beekeeping as their processes of innovation and use of technology in the municipalities of Capitão Poço, Igarapé-Açu and Ourém, located in northeastern Pará State. Specifically it was intended to profile socioeconomic and technological beekeepers, identify the factor dimensions determinants of innovatin and technology, typify the degree of innovation and technology clusters beekeeping and classify beekeepers paraenses according to the index of innovation and technology. To be used as both methods: factor analysis to extradt the main factors representative of the practice of innovation and technology use by beekeepers, besides the construction of an aggregate index for the analysis of clusters that can establish which of them has a higher or lower propensity practice innovations and technogies. The results showed that beekeeping is composed of Pará in most small procuders; uses hand-to-work of low literacy; shows up as an alternative source of income and employment for the rural area and its lack bottlenecks possession of seal inspection by the associationsa and producers, which increases the difficulties in production flow, and the lack of consist and appropriate policies actually the regional reality. Through factor analysis were obtained from two factors named as the technological and innovative aspects and information, the analysis also allowed the construction of an index called the Index of Innovation and Tecnology. As for the groups formed based on the index calculated. Pará has lot of beekeepers in the group o low levels of innovation and techology, thereby constituting a reduced propensity to use such practices by many producers. Regarding the group of medium-index that showed a heterogeneous members, possessing, therefore, the highest value of coefficient of variation. The last group, the largest index, showed only 16% of 78 respondents in the survey, and is where are found almost all the major producers in the region. Finally it was concluded that beekeeping proved to be an importanty tool for generating employment and income in rural areas, but it needs more public attention to his real breakthrough.